Sumudu A domian Decomposition Method for Solving SEIVR Epidemic Model - Joudha, Zainab Mohammed; Al-Azzawi, Saad N. Ali (Iraqi Journal of Science, 2025)
In this paper, we modify an SEIVR model concerning COVID-19 from the first-order system into a multi-fractional order system of differential equations. We also find an approximate solution by using the Sumudu Adomian decomposition method. Furthermore, we try to give qualitative results rather than qualitative results. Numerical simulation is given through a table and graphs which show the efficiency of the method.